DESAIN PENGEMBANGAN DESA WISATA PENERAPAN PENDEKATAN LAY OUT ACTIVITY RELATION CHART (PENGABDIAN DESA PACCING PENGRAJIN SONGKOK TO BONE) - Ahmad Padhil; Darnengsih (LPPM ITEBA, 2023)
Bone Regency is one of the regencies in South Sulawesi Province, geographically it is very strategically located because it is the gateway to the east coast of South Sulawesi which is the west coast of Bone Bay. East of Makassar City, where in this area there is a typical village that produces songkok to bone, which is one of the attributes of traditional Bugis clothing, but in the course of the journey, songkok to bone craftsmen began to decrease because it was only done by people who were old, so with the hope that there would be the development of tourist villages can preserve the local wisdom culture of songkok to bone. The training activity is an introduction to the concept of the Activity Relation Chart (ARC) for young people who already know and understand the concept of village development, especially edu tourism. Young people can already operate the AutoCAD or sketch-up application to develop the concept of a tourism village and primarily educational tourism to develop their respective regions so that they can develop regional potential, especially local wisdom. The Sig. (2-tailed) value is 0.000 <0.05, so it can be seen that there is a significant difference between the training results in the pre-training and post-training data. So it can be concluded that the training that has been carried out has increased the understanding of youth organizations in the Paccing village.